ANALISIS LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT PELABUHAN INDONESIA (PERSERO) SUB REGIONAL BALI NUSA TENGGARA - NI KADEK GITA MAHARANI; KADEK CAHYA DEWI; KETUT VINI ELFAROSA (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted to analyze how work environment and work discipline affect employee performance at PT Pelabuhan Indonesia (Persero) Sub Regional Bali Nusa Tenggara, where employee performance needs improvement. Factors affecting employee performance identified in this research are work environment and work discipline. This research utilized a descriptive quantitative study and the sample for this research consisted of 54 respondents using saturated sampling technique. Multiple linier regressions is used as the data analysis and hypothesis testing utilizing t-statistical and f-statistic to determine the effect of each independent variable on the dependent variable. The research found that work environment and work discipline, each has a positive and significant impact on employee performance and both work environment and work discipline simultaneously have a significant impact on employee performance. The result of the coefficient determination shows the effect work environment and work discipline on employee performance at PT Pelabuhan Indonesia (Persero) Sub Regional Bali Nusa Tenggara is 40%, while the remaining (100% - 40% = 60%) is influenced by other variables outside this study